Prototype Hardware Implementation of a Boost Converter for DCMPFC - Abduljabbar Owaid Hanfesh Alshammery (Wasit Journal of Engineering Sciences)
Power Factor Correction (PFC) is an essential feature of many AC/DC Power Electronics products. The issue of increasing the value of the Power Factor (PF) and increasing efficiency of transferring the power in such applications motivated this work. The integrated circuit NCP1014 was used to implement hardware of 20 W Discontinuous Conduction  Modes Power Factor Correction  (DCMPFC) prototype to be suitable to applications that require good performance, small size, low cost and high efficiency.In this work, a known inductive load is used, and measured the power factor with and without the proposed correction circuit, the results showed an improvement of the power factor up to 40%.The presented results that have been tested in this paper were implemented in a laboratory to show the effectiveness of the proposed system.